Activin A Stimulates Aromatase via the ALK4-Smad Pathway in Endometriosis. (19th October 2016) - Zheng, Juan; Qu, Juan; Lu, Pinhong; Hou, Zhen; Cui, Yugui; Mao, Yundong; Qi, Xiaochen; Ji, Hui; Liu, Jiayin
Abstract : Endometriosis is an estrogen-dependent disease. We previously found that the expression of Activin A was upregulated in the peritoneal fluid of patients with endometriosis. The results of the present study indicated that Activin A induced estradiol secretion and P450arom expression in endometrial stromal cells (ESCs) derived from endometriosis patients. The mechanism of estrogenic synthesis was regulated by the Activin-Smad pathway in endometrial lesions. The data showed that the effect of Activin A on ESCs was partially abrogated by pretreatment with an inhibitor of ALK4 (the type I receptor, ActRIB) and Smad4-siRNA. Cumulatively, these data suggest that Activin A promotes the secretion of estradiol from ESCs by increasing the expression of P450arom via the ALK4-Smad pathway. These findings indicate the ALK4-Smad pathway may promote ectopic lesion survival and development.